KONSEP DALAM MERUMUSKAN VISI, MISI, TUJUAN DAN PROGRAM LEMBAGA PENDIDIKAN ISLAM - Fikri, Moch Sulton Al; Nabila, Sayyid Qutub; Arianto, Aji; Yuliastutik, Yuliastutik (Program Studi Manajemen Pendidikan Islam, 2024)
The era of Society 5.0 and Industrial Revolution 4.0 brought fundamental changes to the educational landscape, requiring Islamic educational institutions to adapt without losing their identity. This article examines the concept of formulating the vision, mission, goals and programs of Islamic educational institutions in the context of the digital era. This research uses a library research method with a descriptive-analytical approach. Data was obtained from primary sources in the form of the Al-Qur'an, Hadith, and the latest publications from reputable Islamic education journals, as well as relevant secondary sources. Data analysis was carried out through the stages of categorization, contextual interpretation and conceptual synthesis. The research results show that these four elements must be formulated based on the integration of modern management and Islamic values ​​interpreted contextually. The main finding is the concept of